Mystical Correct. - Galerie Hohenthal und Bergen, Berlin; Alexejev, Nikita; Becker, Kathrin; Groys, Boris; Oroschakoff, Haralampi G. (Berlin : Salon Verlag, 1997)
Albert, Juri ; Alexejev, Nikita ; Anufriev, Sergej ; Begajan, Armen ; Filippov, Andrej ; Komar & Melamid ; Leiderman, Juri ; Makarevich, Igor ; Elagina, Elena ; Oroschakoff, Haralampi G. ; Pepperstein, Pavel ; Prigov, Dmitri ; Shuravlev, Anatolij ; Zakharov, Vadim ; Zwesdochetov, Konstantin
bibliografie
biografie
Mystical Correct, Galerie Hohenthal und Bergen, Berlin, 1. November bis 21. Dezember 1997
Duits
boek